Evolution of the areal patterns of German and Polish settlement in Milwaukee - Schultz, Gwen (ERDKUNDE, 1956)
Germans and Poles constitute Milwaukee’s two largest nationality groups and together account for more than half of the population. In their settlement patterns, they are fundamentally different. The Germans - the larger group - are almost evenly distributed throughout the city. The Poles, on the other hand, show a strong tendency to cluster together. The present work is an attempt to explain the different settlement patterns. Beginning in 1839, Germans arrived in Milwaukee, which from then on was a transshipment point on the immigrant route to the interior of America. They found favorable climate and abundant natural sources of relief, and the available labor opportunities were known to them. Skilled laborers were additionally drawn from Germany. By 1900, 70% of Milwaukee’s population was of German descent. Their large numbers, the cohesion thus given, preserved the character of the group. Experienced in commerce and many trades, they asserted themselves not only in certain districts but throughout the city. They adapted to the development of the city and integrated themselves into the growing settlement. Poles did not arrive until about 1870, when Milwaukee was the largest German center in the United States. Many Poles with German language skills went there for that very reason. In addition, industry provided employment for unskilled workers. Poles settled near the plant sites in 2 districts. 1. in the NE along the Milwaukee River, 2. in the southern center of the city. While the first area naturally dissipated over time, the main settlement of Poles in the south center of the city remained purely Polish and expanding. Originally, this area offered employment in industry and unlimited, cheap settlement land, and was also the center of church life. r, With its large families, the Polish population group is still growing in numbers today. In the other parts of the city it is hardly noticeable and even decreases in numbers in the NE. But it has the undisputed supremacy in the southern center. The German population has steadily declined in relative numerical importance, but still represents by far the largest percentage of the total population. In the course of Milwaukee’s development through more than a century, the ubiquitous and dominant German element merged with the growing city and now forms an integral part of the urban population.